Improvised profile construction for multimedia databases in e-learning - Premaratne, S.C.; Karunarathne, D.D.; Wikramanayake, G.N.; Hewagamage, K.P.; Dias, G.K.A. (My University, 2005)
E-learning has acquired a prime place in many discussions recently. A number of research efforts around the world are trying to enhance education and training using e-learning. This paper briefly explains one such attempt aimed at designing a system to support video clips in e-learning and explains how profiles of the presenters in video clips can be used to improve the usefulness of e-learning systems. Then it discusses one of the main problems identified in profile construction. Finally, it presents a solution to this problem and describes a novel algorithm for improving the efficiency of the profile construction process.